2018
DOI: 10.1155/2018/5472876
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Clinical Asthma Pathway on Resident Education

Abstract: Clinical pathways for asthma management decrease hospital cost and length of stay; however little is known about the educational impact of pathways on residents. Pediatric residents at a children's hospital (N = 114) were invited to complete a 22-item computerized, anonymous survey 6 months before and 6 months after asthma pathway implementation. The survey assessed pathway use and residents (1) pathway knowledge, (2) attitudes and experiences with managing asthma, and (3) perceived educational benefits. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The Bronx, New York was one of the earliest epicenters for the COVID-19 pandemic and as of November 2020, is the county in the US with the 5th most COVID-19 related deaths [ 21 ]. The prevalence and morbidity of pediatric asthma in the Bronx are the highest in the nation, [ 22 ] including the highest rates of asthma-related hospitalizations and deaths in New York City (NYC) [ 23 , 24 ]. Prior studies have shown that genetic and environmental factors play important roles in the pathogenesis of pediatric asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The Bronx, New York was one of the earliest epicenters for the COVID-19 pandemic and as of November 2020, is the county in the US with the 5th most COVID-19 related deaths [ 21 ]. The prevalence and morbidity of pediatric asthma in the Bronx are the highest in the nation, [ 22 ] including the highest rates of asthma-related hospitalizations and deaths in New York City (NYC) [ 23 , 24 ]. Prior studies have shown that genetic and environmental factors play important roles in the pathogenesis of pediatric asthma.…”
Section: Introductionmentioning
confidence: 99%
“…43 Utilization of evaluation tools allows for individual assessments to provide learner feedback (assessment for learning), followed by aggregated assessment data used for higher stake decisions (assessment of learning). 44 Lastly, the implementation of an assessment scoring tool provides education benefits by standardizing resident exposure to evidence-based medicine, such as the assessment of respiratory distress, and improvement of skills at communicating respiratory status 45 ; remembering that it is the users of the tools, not the tools, which determine the validity of the assessment. 46…”
Section: Discussionmentioning
confidence: 99%